Physicochemical properties of two epoxy resin-based sealants: Topseal® and Adseal™. a comparative study - Julio César Cardona-Hidalgo; José Manuel González-Carreño; Julio César Avendaño-Rueda (Universidad de Antioquia, 2019)
Introduction: a new epoxy resin-based root-canal sealer (AdSeal™) recently appeared on the market. The aim of this study was to evaluate the radiopacity, flow rate, and film thickness of this sealant compared to Topseal®. Methods: the tests were conducted in compliance with ISO 6876:2012 standards. To evaluate radiopacity, 5 discs of each sealant measuring 10 mm in diameter by 1 mm thick were crafted, comparing their radiographic density in mm of aluminum (Al). For flow rate analysis, 0.05 ml of sealant were placed between 2 glass plates under a weight of 120 g for 10 minutes. The diameters of the formed discs were measured with a calibrator and analyzed with the imageJ software. For film thickness analysis, the sealants were placed between 2 glass plates, applying a load of 150N with a universal testing machine (AGIS 5KN) for 10 minutes. Distance between the glass plates was measured using a stereomicroscope at three equidistant points. Results: Topseal® showed more radiopacity (Wilcoxon p < 0.05) and less flow rate than AdSeal™, with statistically significant differences (Anova p = 0.0001863). The film thickness values are above the limit allowed by standard 6876, possibly because of the methodology used in this study; however, no statistically significant difference was found between the sealants (Anova p = 0.4927). Conclusions: the radiopacity and flow rate of AdSeal™ and Topseal® sealants comply with the ISO 6876:2012 standard, but the film thickness values fail to meet the standard.